Integrative analysis of crotonylation-associated genes reveals prognostic and therapeutic targets in gliomas - Yin, Bowen; Fan, Zhuoyang; Yu, Panpan; Li, Jin; Wang, Yilin; Shu, Minfeng (Frontiers in Oncology, 2025)
BackgroundCrotonylation, an emerging epigenetic modification, has been implicated in various biological processes, including tumor progression. However, its role in glioma remains poorly understood. This study aims to investigate the prognostic and therapeutic implications of crotonylation-associated genes in glioma.MethodsCrotonylation levels were assessed by IHC in glioma tissues of varying grades. Key crotonylation-associated genes were identified and analyzed across five glioma datasets. A prognostic risk score was developed using machine learning algorithms and validated in multiple cohorts. Genomic alterations, immune landscapes, and therapeutic responses were examined in relation to the risk score. Single-cell dataset GSE131928 was analyzed to explore the relationship between the risk score and immune cell infiltration. After crotonate treatment of T98G cells, ChIP-seq and qPCR were performed to investigate the effect of crotonylation on gene expression. Finally, PD-1 and GZMB expression levels were assessed in glioma tissues with varying crotonylation levels.ResultsCrotonylation levels were negatively correlated with glioma grade. Crotonylation-related genes stratified patients into two subtypes with distinct overall survival outcomes. High-risk patients exhibited increased somatic mutations, specific copy number variations, and an immunosuppressive tumor microenvironment. The risk score correlated positively with TIDE scores, indicating resistance to immune checkpoint blockade therapy. Single-cell analysis revealed a positive association between the risk score and TAM infiltration. Candidate therapeutic agents tailored for high- and low-risk groups were identified. ChIP-seq and qPCR demonstrated that reduced crotonylation suppressed CXCL1 expression and promoted GZMB expression in the glioma microenvironment.ConclusionCrotonylation-associated genes play a pivotal role in glioma progression and prognosis. The risk score provides a robust tool for patient stratification and treatment guidance, underscoring the importance of crotonylation in glioma biology and its potential as a therapeutic target.